Strategi Pengelolaan Sampah Berkelanjutan di Desa Panton, Kecamatan Tapaktuan, Aceh Selatan - Tendriani Tendriani; Suci Hidayani Putri (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samudra, 2021)
Environmental pollution is a common problem for us, which is increasingly important to solve because it concerns our safety, health, and our lives. Starting from the smallest environment, ourselves, to a wider environment. Waste is a subject matter discussed by people as we know the amount of waste in Indonesia has increased every year, this is due to the population in Indonesia every year has increased, this is because the population of Indonesia is increasing every year and the need for a population is increasing which results in a growing waste population. This causes an unbalanced situation and there must be a movement to utilize waste into something of value, with this utilization it can reduce the level of waste around the Tapaktuan. Garbage is an item that is no longer used and is no longer used. if not handled properly will cause unpleasant odors, a source of various diseases, blockage of drains, and can cause flooding area. For plastic waste to be friendly to nature, management is needed so that besides that it can have added economic value.